Whether pH-metry and investigation of esophageal motor function are necessary for diagnosis and choice of therapy for us today? - O. A. Storonova; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of the publication. To describe various methods of pH-metry and investigation of motor function of the esophagus, to expose a role of these methods for diagnosis statement and choice of treatment.Original positions. Studying of motor function of the esophagus allows to obtain data on intraluminal pressure, coordination and motility of muscles of the esophagus, to carry out differential diagnostics of primary and secondary disorders of this function, differential diagnostics at chest pain of non-cardiac origin, to reveal and estimate defects of peristalsis before antireflux surgery and after surgical intervention, to estimate efficacy of carried out treatment. Manometry is an auxiliary method at carrying out of 24-hour pHmetry of the esophagus as well. 24-hour (or 48-hour) pH-metry is «the gold standard» diagnostics of GERD. Impedance measurement method allows to observe bolus passage in the esophagus without application of X-ray investigation and irradiating of patients, to establish physical properties of refluxate (gas, fluid, mixed), that is important at a choice of treatment.Conclusion. Disorders of esophageal motility can be revealed by various systems of monitoring. Nowadays manometry is informative and available diagnostic method for a doctor. Assessment of physical and chemical properties of refluxate and parameters of peristalsis of the esophagus is necessary for establishment of etiology and pathogenesis of diseases that allows to prescribe specific treatment to the patient.